Assessment of diabetes risk among adult population using Indian diabetes risk score and to correlate with actual capillary blood sugar level: a cross sectional study - Gangwar, Abhinav; Srivastava, Dhiraj Kumar; Kumar, Sandip; Shukla, Sushil Kumar; Sachan, Divyata; Megha, Vashishtha (International Journal Of Community Medicine And Public Health, 2023)
Background: Diabetes is one of the fastest growing health challenges of the 21st century, with the number of adults living with diabetes having more than tripled over the past 20 years. IDRS is pre-screening tool for assessing diabetes mellitus. It is also a non-invasive procedure and less time consuming. Aim were to assess diabetes risk among adult urban population of district Etawah by using Indian Diabetes Risk Score and to correlate it with actual capillary blood sugar status. Methods: The present study was a cross sectional study carried out among 200 adult urban non diabetic population the age group of 30 years and above. The data was collected using predesigned questionnaire followed by capillary blood sugar estimation. The data was collected under following broad heading: socio-demographic profile, Behavioural factor, Indian diabetes risk score and capillary blood sugar estimation. Results: Majority of the participants were in the age group of 35-49 years and Hindu by religion. 62.5% gave history of fast food consumption, nearly half of the participants gave the history of moderate to heavy physical exercise. It was found that 89% of the participants fall under the category of intermediate and high risk category. On application of test of association between IDRS score and actual capillary blood sugar level, strong association exist between the two variables. Conclusions: The present study concludes that IDRS is a powerful tool for screening of high risk group of diabetes. There is a strong association between capillary blood sugar and IDRS score.